Stormwater treatment strategy for the degradation of aircraft deicing fluid at the Joint Base Elmendorf-Richardson in Anchorage, Alaska - Hernandez, Martha Liliana Nunez, author; Carlson, Kenneth, advisor; Sharvelle, Sybil, committee member; Kipper, Matthew, committee member (Colorado State University. Libraries, 2017)
Due to the large volumes of aircraft deicing fluids (ADF) applied by U.S. commercial airports during winter months, stricter pollution control by regulatory agencies has been implemented. Agencies such as the Environmental Protection Agency (EPA), have made several attempts to improve stormwater management practices in airports which has resulted in a decrease of the discharge volumes of ADF contaminated water. However, many U.S. airports continue to explore and develop new strategies to reduce contaminant concentrations to meet the benchmark concentrations required to comply with discharge permits. One of the airports that has not complied with all EPA permits is the Air Force/Army military base Joint Base Elmendorf-Richardson (JBER) located in Anchorage, Alaska. The extremely low temperatures and high average yearly precipitation in Anchorage requires that JBER use a large volume of ADF solution to allow proper aircraft operations. The hundreds of thousand gallons of fluid that are applied during deicing season generates large volumes of contaminated stormwater runoff that is discharged into a nearby water body. Joint Base Elmendorf-Richardson has made several attempts to manage ADF usage on site, but the chemical oxygen demand (COD) and biological oxygen demand (BOD) limits have not been reduced to the standards set by regulatory agencies. To address this issue, JBER contacted the Energy and Water Sustainability Laboratory at Colorado State University (CSU) to determine possible stormwater treatment strategies to be applied on the military base. After considering all treatment technologies currently used at North America airports, the CSU team concluded that biological degradation by subsurface flow constructed wetlands (SFCW) was the most practical option for JBER. The final selection and recommendation was based on extensive literature review and analysis of design criteria, construction, O&M, and maintenance cost, as well as, information of various technologies used in cities with comparable climate conditions to Anchorage. The CSU team developed a series of bench scale experiments that simulated biological degradation in batch SFCWs under ambient and operational conditions relevant to JBERs case. Degradation data was obtained by measuring daily COD concentrations over a 30-day period. A total of 14 experiments at different conditions were performed. Parameters including temperature (5°C vs. 20°C), aeration (aerated vs. non-aerated), ADF composition (all ADF types used by JBER vs. propylene glycol only), and nutrient addition (with nutrients vs. without nutrients) were varied to determine their effect on degradation rates (k), and lag phase in the system. All kinetic parameters were determined and calculated based on first order degradation kinetics in a biological system. Numerical, graphical, and design of experiment (DOE) analyses suggested that the temperature in the system had the highest effect on degradation rates and lag-phases. Analysis of results suggested that the ADFs in stormwater can be treated with the SFCW technology under certain conditions. During winter months, sufficient aeration, nutrient addition and low propylene glycol content are necessary to achieve optimal degradation rates (k=0.11 day-1). However, during warmer months (May-August), it is possible to treat the stormwater under low oxygen, and low nutrient conditions reducing the energy costs of the system. If a stormwater strategy for treatment during warmer months is developed, the stormwater treatment can be optimized in the most economic manner.
Keywords: chemical oxygen demand; stormwater; aircraft deicing fluid; water management; JBER